Infraestructura portuaria en Colombia, un reto permanente para el comercio internacional? (2013)
The Port infrastructure in Colombia represents 90% of its international trade, reason why the efficiency and quality of port infrastructure affects the growth and prosperity of the country. The generation of wellness, and better international trade are a must, keeping low costs at the same time. Colombia has been evaluated by international organisms in its infrastructure and all its components, which were analyzed for this paper finding that the performance wasn´t the best possible. The results were compared with other nations and it was found that the government and private sector must work together looking for a way to implement the necessary changes towards a better future while attacking corruption so the resources applied toward this sector will find its purpose, by investing great amounts of monetary resources, either through foreign investment or internal budgets, with the purpose of improving the existent deficiencies and the reduction of logistics costs, walking towards a better international trade competitiveness result.